2022
DOI: 10.1021/acs.accounts.2c00497
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Association Allosterically Regulates Phospholipase A2 Enzymes and Their Specificity

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS: Water-soluble proteins as well as membrane-bound proteins associate with membrane surfaces and bind specific lipid molecules in specific sites on the protein. Membrane surfaces include the traditional bilayer membranes of cells and subcellular organelles formed by phospholipids. Monolayer membranes include the outer monolayer phospholipid surface of intracellular lipid droplets of triglycerides and various lipoproteins including HDL, LDL, VLDL, and chylomicrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…On the other hand, it has been reported that when a PLA 2 exerts its action on a lipid membrane, the enzyme stabilizes, going from a “closed” conformation in the aqueous solution to an “open” one within the membrane . Clearly, such an allosteric regulation of PLA2 activity is intrinsically related to our findings, where AIDs perform specific lipid remodeling to delay or catalyze lipid cleavage.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…On the other hand, it has been reported that when a PLA 2 exerts its action on a lipid membrane, the enzyme stabilizes, going from a “closed” conformation in the aqueous solution to an “open” one within the membrane . Clearly, such an allosteric regulation of PLA2 activity is intrinsically related to our findings, where AIDs perform specific lipid remodeling to delay or catalyze lipid cleavage.…”
Section: Resultssupporting
confidence: 54%
“…31 On the other hand, it has been reported that when a PLA 2 exerts its action on a lipid membrane, the enzyme stabilizes, going from a "closed" conformation in the aqueous solution to an "open" one within the membrane. 70 Clearly, such an allosteric regulation of PLA2 activity is intrinsically related to our findings, where AIDs perform specific lipid remodeling to delay or catalyze lipid cleavage. Additionally, it has also demonstrated a chain length dependence (membrane packing) of PLA 2 activity, 51 by which we speculate that different acyl chains might undergo the same opposite behavior as in Figure 2d, although to different extents.…”
Section: Aids Differentially Alter Lipid-membrane Structuralmentioning
confidence: 61%
“…The Dennis lab ( Dennis, 2022 ; Mouchlis and Dennis, 2022 ) has made many important insights into the allosteric interaction between lipid bilayer membranes and PLA 2 , especially through their judicial use of hydrogen–deuterium exchange mass spectrometry (HDX-MS) combined with MD simulations to understand the association mechanism of the recombinant human form of group IVA cytosolic (cPLA 2 ), group V secreted (sPLA 2 ), group VIA calcium-independent (iPLA 2 ), and group VIIA lipoprotein-associated phospholipase A 2 (GVIIA Lp-PLA 2 ); they propose that PLA 2 exists in at least three forms: the “closed” form in the cytosol, the “open” membrane-associated “unbound” form, and the “open” membrane-associated “bound” form when binding to a substrate ( Mouchlis and Dennis, 2022 ).…”
Section: Amphipathic Helix-containing Enzymesmentioning
confidence: 99%
“…The fatty acids that comprise phospholipids often differ only in the localization of the single unsaturated bond (e.g., C18:1n-7 or C18:1n-9) or in the conformation of the unsaturated bond (cis and trans isomers of C18:1n-9: cis oleic acid and trans elaidic acid). A further problem is that the MSI technique does not provide information on the relative position (sn-1 or sn-2) of the fatty acids to the glycerol backbone, although the position of the fatty acid is biochemically very important [ 21 , 22 ]. Another limitation is the relatively low spatial resolution of these conventional MSI methods with pixel sizes between 30 and 100 μm [ 23 ].…”
Section: Introductionmentioning
confidence: 99%